Bank Size and Systemic Risk - Laeven, Luc.; Ratnovski, Lev.; Tong, Hui. (Washington, D.C. : International Monetary Fund, 2014)
The proposed SDN documents the evolution of bank size and activities over the past 20 years. It discusses whether this evolution can be explained by economies of scale or 'too big to fail' subsidies. The paper then presents evidence on the extent to which bank size and market-based activities contribute to systemic risk. The paper concludes with policy messages in the area of capital regulation and activity restrictions to reduce the systemic risk posed by large banks. The analysis of the paper complements earlier Fund work, including SDN 13/04 and the recent GFSR chapter on 'too big to fail' subsidies, and its policy message is in line with this earlier work.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet